STATUS OF BMI AND MACRO NUTRITION CONDITIONS OF PABSI ATHLETES IN WEST KALIMANTAN PROVINCE AT THE XX PON EVENT PAPUA - Isti Dwi Puspita Wati; Y. Touvan Juni Samodra; Maharani Fatima Gandasari; Ghana Firsta Yosika; Putra Sastaman (Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi (Penjaskesrek), 2022)
Adequate food intake is one of the keys that will support athlete performance apart from regular and continuous training. An imbalance in food intake will result in athletes experiencing "debt" or even "hoarding" in the body. Periodically this imbalance will be seen in the body mass index of the athlete concerned. This research is a survey research with test and measurement techniques. The sample used in this study were weightlifters and weightlifters in West Kalimantan. The instrument used is a test and measurement of weight and height, as well as food recall 7 x 24 hours. For food recall data, data were collected and entered in the nutrisurvey application. Data analysis using descriptive statistics and correlation test. The results obtained from this study are that there are no athletes who have a normal body mass index and no athletes who have a low energy intake status (below 50% adequacy). In addition, the relationship between body mass index and adequacy of energy intake has a low level of correlation (sig. 0.363). The conclusion obtained from this study is that although the athlete's energy intake adequacy rate is still below 50%, the athlete has a high body mass index. The energy intake adequacy rate was not correlated with the athlete's body mass index